Binding of galectin-1 to breast cancer cells MCF7 induces apoptosis and inhibition of proliferation in vitro in a 2D- and 3D- cell culture model. Issue 1 (December 2016) - Geiger, Pamina; Mayer, Barbara; Wiest, Irmi; Schulze, Sandra; Jeschke, Udo; Weissenbacher, Tobias
Abstract Background Galectin-1 (gal-1) belongs to the family of β-galactoside-binding proteins which primarily recognizes the Galβ1-4GlcNAc sequences of oligosaccharides associated with several cell surface glycoconjugates. The lectin recognizes correspondent glycoepitopes on human breast cancer cells. Galectin-1 is expressed both in normal and malignant tissues. Lymphatic organs naturally possessing high rates of apoptotic cells, express high levels of Galectin-1. Furthermore galectin-1 can initiate T cell apoptosis. Binding of galectin-1 to trophoblast tumor cells presenting the oncofetal Thomsen-Friedenreich (TF) carbohydrate antigen inhibits tumor cell proliferation. In this study we examined the impact galectin-1 has in vitro on cell proliferation, apoptotic potential and metabolic activity of MCF-7 and T-47D breast cancer cells in dependence to their expression of the Thomsen-Friedenreich (TF) tumor antigen. Methods For proliferation and apoptosis assays cells were grown in presence of 10, 30 and 60 μg gal-1/ml medium. Cell proliferation was determined by a BrdU uptake ELISA. Detection of apoptotic cells was done by M30 cyto death staining, in situ nick translation and by a nucleosome ELISA method. Furthermore we studied the impact galectin-1 has on the metabolic activity of MCF-7 and T-47D cells in a homotypic three-dimensional spheroid cell culture model mimicking a micro tumour environment. Results Gal-1 inhibited proliferation of MCF-7 cells (strong expression of the TF epitope) but did not significantly change proliferation of T-47D cells (weak expression of the TF epitope). The incubation of MCF-7 cells with gal-1 raised number of apoptotic cells significantly. Treating the spheroids with 30 μg/ml galectin-1 in addition to standard chemotherapeutic regimes (FEC, TAC) resulted in further suppression of the metabolic activity in MCF-7 cells whereas T-47D cells were not affected. Conclusions Our results demonstrate that galectin-1 can inhibit proliferation und metabolic cell activity and induce apoptosis in breast tumor cell lines with high expression levels of the Thomsen-Friedenreich (TF) antigen in monolayer and spheroid cell culture models.